Decoding Loyalty: A Bibliometric Analysis of the Path from Coffee Consumption to Brand Commitment - Nur Afifah M. Z; Tony Wijaya; Penny Rahmawaty (Research Horizon, 2026)
This study aims to conduct a bibliometric analysis to map trends, cognitive structure, and thematic developments of research on the relationship between consumer behavior, which includes purchase decisions, and the achievement of brand commitments in the Coffeeshop industry. The data was collected from the Scopus database using a combination of the keywords brand loyalty and coffee shop. A total of 170 documents published from 1999 to 2025 were analyzed using VOSviewer. Bibliometric analysis shows that research on loyalty in the coffee shop industry has attracted attention, as evidenced by the significant surge in publications since 2015. In terms of contributors, institutions from South Korea and the United States are the main contributors to literature, while Indonesia occupies the third largest position internationally. In terms of this theme, it is identified that the research is now beyond conventional managerial issues with a shift in attention to integrating the latest contextual factors, such as social media, pandemics, and trust into loyalty models. Fundamentally, loyalty has evolved from just a repeat purchase to a deep psychological commitment driven by customer experience, brand value alignment, and eco-friendly practices. These discoveries serve as an important strategic basis for business actors in a highly competitive market.